2013
DOI: 10.1016/j.ajpath.2013.01.026
|View full text |Cite
|
Sign up to set email alerts
|

FAK-Related Nonkinase Is a Multifunctional Negative Regulator of Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic lung disease whose underlying molecular mechanisms are largely unknown. Herein, we show that focal adhesion kinase-related nonkinase (FRNK) plays a key role in limiting the development of lung fibrosis. Loss of FRNK function in vivo leads to increased lung fibrosis in an experimental mouse model. The increase in lung fibrosis is confirmed at the histological, biochemical, and physiological levels. Concordantly, loss of FRNK function results in incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 79 publications
4
59
0
Order By: Relevance
“…There is emerging recognition of the heterogeneity of IPF pathogenesis, including cell-autonomous behavior and chemoinvasive mediators in the local microenvironment (6). This suggests that each individual patient with IPF has numerous factors that contribute to the phenotype of invasive myofibroblasts (30). The variability in the invasiveness of pulmospheres from control patients and IPF is clearly demonstrated in Figure 3F.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging recognition of the heterogeneity of IPF pathogenesis, including cell-autonomous behavior and chemoinvasive mediators in the local microenvironment (6). This suggests that each individual patient with IPF has numerous factors that contribute to the phenotype of invasive myofibroblasts (30). The variability in the invasiveness of pulmospheres from control patients and IPF is clearly demonstrated in Figure 3F.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our findings showing high levels of FAK phosphorylation in fibroblasts of OP are consistent with the idea that FAK has a key role in development of lung fibrosis. To our knowledge, three studies (two immunohistochemical 46,47 and one western blotting 48 studies) suggested that phosphorylated FAK levels were high in lung fibroblasts from IPF/UIP patients. However, in the three studies, the results were analyzed by comparison with normal human lung tissues or cultured lung fibroblasts from healthy subjects as normal controls, but not with intraluminal buds of OP as we examined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetized, tracheostomized, paralyzed, and mechanically ventilated mice were used during all static P-V loop measurements (as a measure of lung compliance). Collagen deposition was quantified biochemically by measuring hydroxyproline levels or detecting collagen-1 in the lung tissue extracts by immunoblotting analysis (58). Fibrosis development was assessed by quantitation of α-SMA expression in the lung tissue extracts by immunoblotting analysis.…”
Section: +mentioning
confidence: 99%
“…Fibrosis development was assessed by quantitation of α-SMA expression in the lung tissue extracts by immunoblotting analysis. Lung lavage was performed to determine total wbc counts or cell differentials as described previously (58). All animal protocols were performed according to guidelines approved by the Cleveland Clinic Institutional Review Board.…”
Section: +mentioning
confidence: 99%